2022
DOI: 10.21037/tcr-22-436
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors and individualized nomograms predicting overall survival in stage IV rectal cancer patients with different metastatic status: a SEER-based study

Abstract: Background: The prognosis of rectal cancer patients with different metastatic status was significantly different. Our aim was to identify prognostic factors for metastatic rectal cancer (mRC) patients with different metastatic status and to construct specific nomograms to predict overall survival (OS).Methods: This study retrospectively analyzed mRC patients from 2010 to 2016 in the Surveillance, Epidemiology, and End Results Program database. All patients were ultimately divided into four groups: synchronous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
2
1
0
Order By: Relevance
“…Shida et al found that detecting metastasis in more than one area was a poor prognostic factor (10). Similarly, in the study of Ge et al, it was found that the prognosis of multiple metastases was poor (11). In our study, more than two metastases were found to be poor prognostic, confirming previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Shida et al found that detecting metastasis in more than one area was a poor prognostic factor (10). Similarly, in the study of Ge et al, it was found that the prognosis of multiple metastases was poor (11). In our study, more than two metastases were found to be poor prognostic, confirming previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…In more than one study, lung metastasis is a good prognosis indicator in rectal cancer, and in our study, it was found to not affect the prognosis ( 12 , 13 ). In many studies, liver, bone, and non-regional lymph node metastases are worse prognostic than other metastases ( 9 , 11 , 12 ). In our study, we found that these metastatic regions were poor prognostic.…”
Section: Discussionmentioning
confidence: 99%
“…CSS can be prognosed by nine independent variables. The nine significant prognostic factors identified by Cox analysis were also found in previous studies ( 33 35 ). Although we found no new prognostic factors affecting rectal cancer, the prognostic factors that we identified were easily obtained from practical clinical work.…”
Section: Discussionsupporting
confidence: 82%